Literasi Ekonomi Syariah di SMPN 8 Kecamatan Pelalawan - Assyifa, Zubaidah; Winario, Mohd; Sudirman, Wahyu Febri Ramadhan; Amalia, Nala; Amelia, Nur (EL-EMIR INSTITUTE, 2024)
This community service was conducted in Pelalawan Regency, Riau Province. The object was SMPN 8, Pelalawan District. This community service aims to socialize Islamic economics in junior high schools. The results of this community service indicate that: 1) The success of the target number of training participants. 2) Achievement of activity objectives. 3) Achievement of planned material targets. 4) The ability of participants to master the material. Overall, this community service activity can be said to be successful. This success, in addition to being measured from the four components above, can also be seen from the satisfaction of participants after participating in the activity because the community service provides the opportunity to ask as many questions as possible and when the community service provides questions, they can be answered by students, especially for students who can answer are given prizes. The benefits obtained by participants are knowledge and understanding of the principles of Islamic economics.